Emotional Control, Styles of Coping with Stress and Acceptance of Illness among Patients Suffering from Chronic Somatic Diseases. (8th May 2013) - Janowski, Konrad; Kurpas, Donata; Kusz, Joanna; Mroczek, Bożena; Jedynak, Tomasz
Abstract The purpose of this study was to analyse the associations of emotional control with sociodemographic and clinical variables in a sample of patients with a range of chronic somatic diseases. The relationships between emotional control, coping styles and adjustment to the disease were investigated. The sample consisted of 300 patients with the mean age of 54.60 ± 17.57 years. Courtauld Emotional Control Scale was used to measure the patients' tendency to suppress negative emotions, Coping Inventory for Stressful Situations was used to measure coping styles and Acceptance of Illness Scale was applied to determine adjustment to the disease. Patients with neurological conditions showed significantly lower suppression of anger. Levels of emotional control were found to be related to gender, age and educational level but not to the place of residence. Task‐oriented style of coping with stress correlated positively with suppression of depression and anxiety, whereas acceptance of illness correlated negatively with suppression of anger. Levels of emotional control are only weakly related to the type of diagnosis; however, some clinical samples may show lower suppression of anger. Suppression of negative emotions is weakly related to adjustment indicators such as certain coping styles and acceptance of illness. Copyright © 2013 John Wiley & Sons, Ltd.